Analisis Rasch pada Skala Efikasi Diri Akademik Praktikum Konseling - Christiana, Ratih; Krisphianti, Yuanita Dwi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to analyze the academic self-efficacy scale at counseling practicum up to the item and item level. The method in this study uses a quantitative method, aimed at 18 undergraduate students of the fifth semester guidance and counseling study program at Nusantara University PGRI Kediri. Data collection techniques in this study were in the form of a scale developed by researchers, namely the academic self-efficacy scale of counseling practicum. Analysis of the data used is the Rasch analysis which aims to provide overall information about the quality of student response patterns and quality on the academic self-efficacy scale of counseling practicum. The result of the analysis showed that were 27 items of counseling practicum academic self-efficacy scale items that were declared valid and reliable, along have been validated by three experts. The item separation value of 3,29 is rounded to 3, meaning that there are three types of items on the academic self-efficacy scale in counseling practice, namely: (1) difficult academic self-efficacy scale items, (2) medium academic self-efficacy scale items, (3) easy academic self-efficacy scale items.